Concordance in diagnostic testing for respiratory pathogens of bighorn sheep - Daniel P. Walsh; E. Frances Cassirer; Michael D. Bonds; Daniel R. Brown; William H. Edwards; Glen C. Weiser; Mark L. Drew; Robert E. Briggs; Karen A. Fox; Michael W. Miller; Sudarvili Shanthalingam; Subramaniam Srikumaran; et al. (Wildlife Society Bulletin)
ABSTRACT Reliable diagnostic tests are essential for disease investigation and management. This is particularly true for diseases of free‐ranging wildlife where sampling is logistically difficult precluding retesting. Clinical assays for wildlife diseases frequently vary among laboratories because of lack of appropriate standardized commercial kits. Results of diagnostic testing may also be called into question when investigators report different etiologies for disease outbreaks, despite similar clinical and pathologic findings. To evaluate reliability of diagnostic testing for respiratory pathogens of bighorn sheep (Ovis canadensis), we conducted a series of ring tests across 6 laboratories routinely involved in detection of Mycoplasma ovipneumoniae, Pasteurellaceae, lktA (the Pasteurellaceae gene encoding leukotoxin), and 3 reference laboratories. Consistency of results for replicate samples within laboratories was high (median agreement = 1.0). Agreement between laboratories was high for polymerase chain reaction (PCR) detection of M. ovipneumoniae and culture isolation of Mannheimia spp. and Bibersteinia trehalosi (median agreement = 0.89–0.95, Kappa = 0.65–0.74), and lower for PCR detection of Mannheimia spp. lktA (median agreement = 0.58, Kappa = 0.12). Most errors on defined status samples were false negatives, suggesting test sensitivity was a greater problem than specificity. However, tests for M. haemolytica and lktA yielded some false positive results. Despite differences in testing protocols, median agreement among laboratories and correct classification of controls for most agents was ≥0.80, meeting or exceeding the standard required by federal proficiency testing programs. This information is valuable for interpreting test results, laboratory quality assessments, and advancing diagnosis of respiratory disease in wild sheep. Published 2016. This article is a U.S. Government work and is in the public domain in the USA.